Danças circulares sagradas : potencialidades interculturais na formação de educadores - Silva, Solange Mara Moreschi (2017)
This research focuses on Sacred Circular Dances as an object of study as a Movement that generates human experience. The language of dance, which is a symbolic knowledge, expressed in gestures, music and archetypes of cultures, brings a new body consciousness, produces meanings for the education of the body that is constituted in relation to the Other. The purpose of this study is to understand the potential of Sacred Circular Dances for the formation of educators in the perspective of Intercultural Education, with the body as a locus of learning and analysis. Interculturality adopts a pragmatic stance of relationships, studies communication between different cultures and people, to understand how they create meanings, gestures, actions, words for other subtle forms of communication and how they use it to live together. We understand the interculturality and centrality of the body in the education of the person, especially for an education focused on self-recognition in relation to the Other. The dance that educates and communicates the specific and differentiated ways of being of each group and people, is the didactic resource of investigation in the formative action of educators. The research was carried out through the DCS workshops with a group of nine educators and an educator of the Antônio Garcia State School in the Pantanal city of Poconé in Mato Grosso, being characterized as an action research linked to an extension project developed by COEDUC / UFMT With CEFAPRO / SEDUC-MT. Individual interviews were carried out, an imaginary record of the lived experience and later analyzed with the collaborators / dancers, and also with the application of a questionnaire before and after the experiences and conversation wheels. The analysis of the data is guided by the triangulation of methods with the data that were collected in different times and spaces experienced in the dancing bodies delimited by elements present in the dances of the Sagrada peoples, which imply in re-signification of the daily educational practices, as well as their roles as Conscious and active subjects, including in other forms of relations with nature. In the context of education that passes through the body, dance as an expression of identity and culture, leads us to understand it as a social practice, which expresses marks of the history of interethnic relations and how it continues to give meaning and specific meanings in Different territories (spaces). The dialogue with the authors and the data produced in the research shows that the pedagogical practice based on the Holy Circular Dances has great potential of education of the body, being an educational experience that can only be transformative because it dares to value the culture of the Other and The different identities.